Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Higher Order Thinking Skills (HOTS) - Selirowangi, Nisaul Barokati; Aisyah, Nur; Rohmah, Lailatur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of writing this work is to determine the application of the Problem Based Learning Model to Improve Higher Order Thinking Skills (HOTS). This research uses a narrative qualitative method based on interviews and observations at classroom action research (PTK) at Al-Ishlah Vocational High School class raise Higher Order Thinking Skills (HOTS). The five PBL steps followed by teachers involve student orientation to the problem, student organization in learning, investigative guidance, development of work results, and analysis and evaluation of the problem solving process. The results of the first cycle show that PBL has not been completely successful in improving student learning outcomes. An in-depth evaluation of the understanding and application of PBL is needed. The second cycle recorded significant improvements, with the average student assignment score increasing. Teacher reflection shows several obstacles, such as lack of attention from students and limited interaction between them. The implementation of PBL at Al-Ishlah Vocational School has a positive impact on students' HOTS abilities. There was a significant shift in the distribution of average student grades between the first and second cycles. The PBL model, according to the steps, based on research shows that PBL can be an effective approach to improving the quality of learning at Al-Ishlah Vocational School.